Using the Mitigation Options Tool (CCAFS-MOT): Case studies - Feliciano, Diana; MacSween, Kirsten (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Key messages ◼ The CCAFS Mitigation Options Tool (CCAFS- MOT) enables quick identification and comparison of mitigation options for agriculture with minimal training or data requirements. ◼ The tool is appropriate for generating high-level scenarios for discussion by project planners, consultants, extension services, advisors to policy-makers, teachers, and researchers. ◼ Several users considered CCAFS-MOT easy to use and were interested in continuing use. ◼ Many users were not familiar with greenhouse gas (GHG) emission accounting tools before experiencing the CCAFS-MOT.